Global response of glacier runoff to twenty‐first century climate change. Issue 4 (1st April 2014) - Bliss, Andrew; Hock, Regine; Radić, Valentina
Abstract The hydrology of many important river systems in the world is influenced by the presence of glaciers in their upper reaches. We assess the global‐scale response of glacier runoff to climate change, where glacier runoff is defined as all melt and rain water that runs off the glacierized area without refreezing. With an elevation‐dependent glacier mass balance model, we project monthly glacier runoff for all mountain glaciers and ice caps outside Antarctica until 2100 using temperature and precipitation scenarios from 14 global climate models. We aggregate results for 18 glacierized regions. Despite continuous glacier net mass loss in all regions, trends in annual glacier runoff differ significantly among regions depending on the balance between increased glacier melt and reduction in glacier storage as glaciers shrink. While most regions show significant negative runoff trends, some regions exhibit steady increases in runoff (Canadian and Russian Arctic), or increases followed by decreases (Svalbard and Iceland). Annual glacier runoff is dominated by melt in most regions, but rain is a major contributor in the monsoon‐affected regions of Asia and maritime regions such as New Zealand and Iceland. Annual net glacier mass loss dominates total glacier melt especially in some high‐latitude regions, while seasonal melt is dominant in wetter climate regimes. Our results highlight the variety of glacier runoff responses to climate change and the need to include glacier net mass loss in assessments of future hydrological change.